Pengaruh Debt to Equity Ratio (DER), Return On Assets (ROA), size dan bonus plan terhadap perataan laba - ARTAMEVIA ARINDITA, TYA; WAHYU WIDATI, LISTYORINI WAHYU WIDATI (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Income smoothing is one way that companies do to manipulate company profit if company profit fluctuates, investors will think again to invest in the company, this will trigger the practice of income smoothing. One example is a manufacturing company in the banking sub-sector. This study aims to analyze and test the debt to equity ratio, return on assets, size and bonus plan on earnings management. The population used in this study is the banking manufacturing sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the last four years, 2017-2020 with a final sample of 122. The sampling method used in this study used a purposive sampling technique. The data analysis technique used multiple linear regression analysis using the SPSS 22 program. The results of this study partially explained that the debt to equity ratio, return on assets and bonus plan had no effect on income smoothing.. Meanwhile, size has a positive and significant effect on income smoothing.